Pentablock star shaped polymers in less than 90 minutes via aqueous SET-LRP. Issue 1 (28th October 2015) - Aksakal, R.; Resmini, M.; Becer, C. R.
Abstract : The synthesis of core-first multi-block star-shaped copolymers via aqueous SET-LRP has been reported for the first time. Abstract : The synthesis of multi-block star-shaped copolymers via SET-LRP in aqueous solution has been reported for the first time. This aqueous polymerization technique allows rapid and direct access to acrylamide based star-shaped polymers. It is possible to synthesize an A-B-A-B-C penta-block copolymer in <90 minutes in total. To achieve this, we have investigated a water-soluble 3-arm initiator based on a glycerol structure for the first time. Using N -isopropylacrylamide 3-arm star-shaped polymers were prepared with DP = 60 to 240 with full conversions in <30 minutes with polydispersities <1.11. The scope of the reaction was demonstrated by synthesizing diblock copolymers using a combination of NIPAM, DMA and HEAm in different ratios. In addition a sequence controlled 3-arm pentablock copolymer has been obtained with excellent control over molecular weight distribution (PDI < 1.14) as evidenced by GPC, 1 H NMR, and MALDI-TOF MS.